A comprehensive evaluation of monochloramine disinfection on water quality, Legionella and other important microorganisms in a hospital. (1st February 2021) - Lytle, Darren A.; Pfaller, Stacy; Muhlen, Christy; Struewing, Ian; Triantafyllidou, Simoni; White, Colin; Hayes, Sam; King, Dawn; Lu, Jingrang
Highlights: Monochloramine was reliably added to a hospital's hot water supply. Adding monochloramine to a hospital's hot water significantly decreased Legionella . Monochloramine reduced HPCs, Pseudomonas aeruginosa and Vermamoeba vermiformis . No signs of nitrification were observed following monochloramine addition. Treatment did not have other negative unintended water quality consequences. Abstract: Opportunistic pathogens such as Legionella are of significant public health concern in hospitals. Microbiological and water chemistry parameters in hot water throughout an Ohio hospital were monitored monthly before and after the installation of a monochloramine disinfection system over 16 months. Water samples from fifteen hot water sampling sites as well as the municipal water supply entering the hospital were analyzed using both culture and qPCR assays for specific microbial pathogens including Legionella, Pseudomonas spp., nontuberculous Mycobacteria [NTM], as well as for heterotrophic bacteria. Legionella culture assays decreased from 68% of all sites being positive prior to monochloramine addition to 6% positive after monochloramine addition, and these trends were parallel to qPCR results. Considering all samples, NTMs by culture were significantly reduced from 61% to 14% positivity ( p <0.001) after monochloramine treatment. Mycobacterium genus-specific qPCR positivity was reduced from 92% to 65%, but the change was not significant. Heterotrophic bacteria (heterotrophic bacteria plate counts [HPCs]) exhibited large variability which skewed statistical results on a per room basis. However, when all samples were considered, a significant decrease in HPCs was observed after monochloramine addition. Lastly, Pseudomonas aeruginosa and Vermamoeba vermiformis demonstrated large and significant decrease of qPCR signals post-chloramination. General water chemistry parameters including monochloramine residual, nitrate, nitrite, pH, temperature, metals and total trihalomethanes (TTHMs) were also measured. Significant monochloramine residuals were consistently observed at all sampling sites with very little free ammonia present and no water quality indications of nitrification (e.g., pH decrease, elevated nitrite or nitrate). The addition of monochloramine had no obvious impact on metals (lead, copper and iron) and disinfection by-products.